« Topologie de la démesure » : entretien avec Félie-Line Lucol, artiste-plasticienne - Frédéric Lefrançois; Félie-Line Lucol (Études Caribéennes)
This interview synthesizes artist statements collected in a series of interviews with Félie-Line Lucol conducted by Frédéric Lefrançois, with reference to the paper presented during the conference “Artistic Cartographies and Topologies” which was held on 18 December 2017, at the Campus of Fouillole, Guadeloupe, FWI, University of the French Antilles.